An assessment of financial data processing at minerals marketing corporation of Zimbabwe - Ritsire, Linda Nyasha (Midlands State University, 2017)
This project was undertaken to try and assess the financial data processing at MMCZ. The problem of financial statements being unreliable at MMCZ led to the need for the research. The research was conducted using questionnaires and literature survey methods. Closed ended questionnaires were used to gather information which led to return rate. The sampled population was obtained through the use of judgmental sampling. Several recommendations which were drawn from this are that entities are facing challenges in implementing the policy and the systems. From the finding recommendations were obtained for the corporation to consider adopting.